DIRECTIVE SPEECH ACTS ANALYSIS: RED SHOES AND THE SEVEN DWARFS MOVIE (2019) - Nyoman risma ayu Pradnyani; Putu Devi Maharani; Komang Dian Puspita Candra (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
The title of this article is Directive Speech Acts Analysis: Red Shoes and The Seven Dwarfs Movie (2019). This article focuses on finding utterances that contain directive speech acts. The goals of this article are to analyze the types of directive speech acts used by the characters in Red Shoes and The Seven Dwarfs Movie. Movie usually contain meaning and messages in every utterance that is produced. The utterances used can provide references to distinguish the types of utterances that contain directive speech acts. To answer the problem of this article, the researcher has analyzed based on the theory by Kreidler (1998). Descriptive qualitative method is the method used in analyzing the data by explaining descriptively the utterances that contain directive speech acts into the types based on Kreidler’s (1998) classification. The results of this study are presented in three types of directives, the first is command, the second is request, and last is suggestion.